Common Threads: Aphidicolin-Inducible and Folate-Sensitive Fragile Sites in the Human Genome - Lokanga, Rachel Adihe; Kumari, Daman; Usdin, Karen (Frontiers in Genetics, 2021)
The human genome has many chromosomal regions that are fragile, demonstrating chromatin breaks, gaps or constrictions on exposure to replication stress. Common fragile sites (CFSs) are found widely distributed in the population, with the largest subset of these sites being induced by aphidicolin (APH). Other fragile sites are only found in a subset of the population. One group of these so-called rare fragile sites (RFSs) is induced by folate stress. APH-inducible CFSs are generally located in large, A+T-rich transcriptionally active genes. In contrast, all the folate-sensitive sites mapped to date consist of transcriptionally silenced CGG-microsatellites. The molecular basis of all the folate-sensitive fragile sites is thus likely to be very similar and different in keyways from the APH CFSs. The folate-sensitive FSs include FRAXA, that is associated with Fragile X syndrome, the most common heritable form of intellectual disability. Both CFSs and RFSs can cause chromosomal loss and rearrangement. Recent work suggests that both APH-inducible fragile sites and FRAXA undergo Mitotic DNA synthesis (MiDAS) when exposed to APH or folate stress respectively. Interestingly blocking MiDAS in both cases prevents chromosome fragility but increases the risk of chromosome mis-segregation. MiDAS of both APH-inducible and FRAXA involves POLD3 and thus, is likely to proceed via some form of break-induced replication (BIR). This review will discuss the recent work that highlights the similarities and differences between these two groups of fragile sites and the growing evidence for the presence of many more novel fragile sites in the human genome.